Satmikarana with Triphala Churna: A Pilot Single-arm Interventional Study for Tobacco (Masheri) De-addiction - Nitesh Raghunath Joshi; Bhakti Bhau Mehta (Journal of Ayurveda, 2025)
Introduction: Masheri, a popular smokeless tobacco product, is extremely harmful to one’s health, especially for those living in rural areas. Traditional de-addiction techniques frequently entail a sudden stop, which causes withdrawal symptoms that make long-term recovery more difficult. The Satmikarana process of Ayurveda provides a method of progressive decrease by substituting healthy habits for detrimental ones. The efficacy of Triphala Churna in place of Masheri in the Satmikarana technique is assessed in this study.